Meningioma: A Pathology Perspective. Issue 1 (15th February 2021) - Toland, Angus; Huntoon, Kristin; Dahiya, Sonika M
Abstract: Meningiomas are dural-based neoplasms that account for ∼37% of all intracranial tumors in the adult population. They can occur anywhere within the central nervous system and have a predilection for females. The World Health Organization classifies meningiomas into 3 grades based on increased risk of recurrence and associated mortality in grade III tumors. Although most tumors are categorized as low-grade, up to ∼15%-20% demonstrate more aggressive behavior. With the long-recognized association with neurofibromatosis type 2 gene mutation, putative driver mutations can be attributed to ∼80% of tumors. Several germline mutations have also been identified in some cases of familial meningiomatosis such as SMARCE1, SUFU, PTEN, and BAP1 . Finally, in addition to genetic data, epigenetic alterations, specifically deoxyribonucleic acid methylation, are being increasingly recognized for their prognostic value, potentially adding objectivity to a currently subjective grading scheme.